Marketing information products and services : a primer for librarians and information professionals editors, Abhinandan K. Jain ... [et al.].. - Jain, Abhinandan K. (Tata McGraw-Hill Pub. Co., 1999)
Contributed articles presented at a workshop held in 1994.